2023
DOI: 10.3390/pathogens12091165
|View full text |Cite
|
Sign up to set email alerts
|

Psittacosis: An Underappreciated and Often Undiagnosed Disease

Zygmunt F. Dembek,
Jerry L. Mothershead,
Akeisha N. Owens
et al.

Abstract: The bacterial agent Chlamydia psittaci, and the resulting disease of psittacosis, is a little-known and underappreciated infectious disease by healthcare practitioners and in public health in general. C. psittaci infections can cause significant psittacosis outbreaks with pandemic potential, with person-to-person transmission being documented in the last decade. In this publication, we review the pathogen and its disease, as well as examine the potential for genetic manipulation in this organism to create a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 87 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…Rare complications could include myocarditis, encephalitis, hepatitis, keratoconjunctivitis, acute respiratory distress syndrome, and multiple-organ failure, with development of ocular lymphoma [ 8 ]. Serious or life-threatening illness can occur when the signs of psittacosis are not recognized [ 9 , 10 ]. The main route of human infection is by the inhalation of aerosolized organisms from dried avian feces or respiratory tract secretions of infected birds [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rare complications could include myocarditis, encephalitis, hepatitis, keratoconjunctivitis, acute respiratory distress syndrome, and multiple-organ failure, with development of ocular lymphoma [ 8 ]. Serious or life-threatening illness can occur when the signs of psittacosis are not recognized [ 9 , 10 ]. The main route of human infection is by the inhalation of aerosolized organisms from dried avian feces or respiratory tract secretions of infected birds [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although C. psittaci is an obligate intracellular bacterium, it has been documented in environmental samples and waters as reticulate bodies that may represent a long-term environmental reservoir of the bacterium [ 9 ]. Although previous studies in infected mares reported reproductive (such as genital infection, occasional abortion, and infertility) and respiratory signs (pneumonia, conjunctivitis, and polyarthritis) attributed to C. psittaci [ 18 , 19 ] and rarely to C. abortus , the relationships between equine abortion and chlamydial infection are still being studied [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the Chlamydiaceae family, the genus Chlamydia contains 13 species ( LPSN, 2024b ), 3 of which are the most relevant as human pathogens. Chlamydia trachomatis is the main bacterial cause of sexually transmitted infections and the leading agent of infectious blindness worldwide ( WHO, 2018 ; WHO, 2022 ), C. pneumoniae is a common etiology of atypical pneumoniae ( Aliberti et al., 2021 ), and C. psittaci causes psittacosis, a globally distributed and potentially fatal zoonotic disease transmitted to humans mainly by exposure to birds ( Dembek et al., 2023 ; Liu et al., 2023 ).…”
mentioning
confidence: 99%